Dominate approach of MW-mile method for cost allocation of deregulated power system / Faizul Rizal Mohamed Tazudin - Mohamed Tazudin, Faizul Rizal (2003)
This proposal introduces the methodology to determine the transmission cost or pricing among users in power systems based on topological analysis of power flows in transmission. The cost allocation is concerned by treating transmission company (transco) as a separate business of transporting energy from any generator (genco) to any area supplier (discos). The cost allocations are calculated based on the MW-mile dominant approach. The methodology proposed is capable to determine the network usage by any load and generator by accumulating all the costs of each load/generator that obtained from every tine flow. The dominant approach comprises of two types of cost allocations namely extended dominant and extended absolute methods. The load flows are an important part of power system used to estimate the costs of transmission. The cost allocation is important and beneficial to the agents in making investment decision in relation to the power transfer. The proposed method also is able to analyze the cost allocation of power systems both normal operating conditions and also with various powers transfer condition. Comparative study has been carried out on the IEEE 9 Reliable Test System (RTS) of 9 bus and 24 bus to verify the effectiveness of the methods in allocating the cost of each bus.